Amyloid imaging with [18F]florbetapir in geriatric depression: early‐onset versus late‐onset. (21st October 2014) - Tateno, Amane; Sakayori, Takeshi; Higuchi, Makoto; Suhara, Tetsuya; Ishihara, Keiichi; Kumita, Shinichiro; Suzuki, Hidenori; Okubo, Yoshiro
<x xml:space="preserve">Abstract</x> Background We examined patients with mild cognitive impairment (MCI) with a history of geriatric depression (GD) and healthy controls (HC) to evaluate the effect of beta‐amyloid (Aβ) pathology on the pathology of GD by using [18F]florbetapir PET. Methods Thirty‐three elderly patients (76.7 ± 4.2 years) and 22 healthy controls (HC; 72.0 ± 4.5 years, average ± SD) were examined by [18F]florbetapir positron emission tomography (PET) to quantify the standard uptake value ratio (SUVR) as the degree of amyloid accumulation, by MRI to determine the degree of atrophy, by Mini‐Mental State Examination for cognitive functions, and by Geriatric Depression Scale for the severity of depression, and by Clinical Dementia Rating for activity of daily living (ADL). The cut‐off value of 1.08 for SUVR was defined as Aβ‐positive. Results Of the patients and HC, 39.4% and 27.3%, respectively, were beta‐amyloid‐positive. The onset age of GD was significantly correlated with SUVR (r = 0.44, p < 0.01). Compared to patients without Aβ (GD‐Aβ), patients with Aβ (GD + Aβ) did not differ in terms of age, cognitive function, severity of depression and ADL, and brain atrophy. GD + Aβ had significantly older average ± SD age at onset of GD (73.6 ± 7.1 versus 58.7 ± 17.8, p < 0.01) and significantly shorter average ± SD time between onset of GD and PET scan day (3.1 ± 5.2 years versus 18.1 ± 18.6 years, p < 0.001) than GD‐Aβ. Conclusions Our results showed that the rate of Aβ positivity was higher in late‐onset GD and that onset‐age was associated with SUVR, suggesting that the later the onset of GD, the more Aβ pathology affected its onset. Copyright © 2014 John Wiley & Sons, Ltd.